The Role of Social Media as a Digital Marketing Strategy for Hotels in Yogyakarta (Case Study at Sahid Raya Hotel & Convention Center) - Purnomo, Agus Setijo; Setiawan, Budi (Indonesian Journal of Advanced Research, 2025)
The rapid advancement of digital technology has reshaped marketing strategies within the hospitality industry, particularly in Yogyakarta—one of Indonesia’s premier tourist destinations. Social media is no longer merely a communication channel but has evolved into a potent promotional tool for building brand awareness, enhancing engagement, and influencing travelers’ accommodation decisions. This study aims to analyze the role of social media in the digital marketing strategies of four-star hotels in Yogyakarta, with a specific focus on Instagram and TikTok as the most prevalent platforms. Employing a qualitative methodology, the research incorporates engagement metrics analysis (likes, comments, and interaction levels), a survey of 250 hotel guests, and in-depth interviews with eight hotel marketing managers. Findings indicate that Instagram plays a dominant role in crafting a hotel’s visual identity and appealing to aesthetically driven travelers, whereas TikTok is more effective in reaching Generation Z and millennial audiences through concise, creative, and interactive content. The combined leverage of these platforms enhances the hotel’s brand image, market positioning, and visibility, while simultaneously fostering stronger guest relationships. In conclusion, social media–driven marketing strategies effectively bolster hotel performance in Yogyakarta. It is recommended that hotels establish robust digital marketing teams and optimally utilize interactive platform features.